99 questions/Solutions/14

From HaskellWiki
Jump to navigation Jump to search
The printable version is no longer supported and may have rendering errors. Please update your browser bookmarks and please use the default browser print function instead.

(*) Duplicate the elements of a list.

dupli [] = []
dupli (x:xs) = x:x:dupli xs

or, using list comprehension syntax:

dupli list = concat [[x,x] | x <- list]

or, using the list monad:

dupli xs = xs >>= (\x -> [x,x])

or, using concatMap:

dupli = concatMap (\x -> [x,x])

also using concatMap:

dupli = concatMap (replicate 2)

or, using foldl:

dupli = foldl (\acc x -> acc ++ [x,x]) []

or, using foldr:

dupli = foldr (\ x xs -> x : x : xs) []

or, using silliness:

dupli = foldr (\x -> (x:) . (x:)) []

or, even sillier:

dupli = foldr ((.) <$> (:) <*> (:)) []

and here is the proof that ((.) <$> (:) <*> (:)) = (\y z -> y:y:z):

(.) <$> (:) <*> (:) =
((.) <$> (:)) <*> (:) = -- (<$>) is infixl 4, (<*>) is infixl 4
((.) . (:)) <*> (:) = -- (<$>) == (.) for functions
(\x -> (.) (x:)) <*> (:) = -- definition of (.)
\y -> (\x -> (.) (x:)) y (y:) = -- definition of (<*>) for functions
\y -> ((.) (y:)) (y:) = -- beta reduction (applying y to (\x -> (.) (x:)))
\y -> (y:) . (y:) = -- changing (.) to its prefix form
\y -> (\z -> (y:) ((y:) z)) = -- definition of (.)
\y z -> y:y:z -- making it look nicer